2021
DOI: 10.1016/j.jtumed.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole-body vibration on abdominal thickness and sitting ability in children with spastic diplegia

Abstract: Objective Reduced muscle and bone mass, improper muscle function, and varying degrees of mobility dysfunctions are the main complications of cerebral palsy (CP). Many children with CP also present with poor abdominal muscle activation. Whole-body vibration (WBV) is a unique approach for enhancing strength and motor abilities in several clinical conditions. This study aimed to determine the influence of a 12-week WBV intervention on the thickness of the abdominal muscles and the sitting ability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, no significant effect was observed on gastrocnemius muscle thickness (p = 0.645) [7]. Another study [15] reported that post-treatment values demonstrated significant improvement in the parameters in favor of the experimental group (p < 0.05), as there was an improvement in the thickness of the four abdominal muscles when compared to the control group (external oblique: F = 38.783, internal oblique: F = 99.547, transverse abdominis: F = 111.557, and rectus abdominis: F = 129.940, p < 0.05).…”
Section: Muscle Thicknessmentioning
confidence: 94%
See 1 more Smart Citation
“…However, no significant effect was observed on gastrocnemius muscle thickness (p = 0.645) [7]. Another study [15] reported that post-treatment values demonstrated significant improvement in the parameters in favor of the experimental group (p < 0.05), as there was an improvement in the thickness of the four abdominal muscles when compared to the control group (external oblique: F = 38.783, internal oblique: F = 99.547, transverse abdominis: F = 111.557, and rectus abdominis: F = 129.940, p < 0.05).…”
Section: Muscle Thicknessmentioning
confidence: 94%
“…The intensity of WBV depends on factors like amplitude, frequency, and oscillation magnitude [9,14]. Low-amplitude, low-frequency stimulation is thought to enhance muscle strength and potentially reduce spasticity and improve musculoskeletal parameters [9,15]. External factors, such as body positioning and exposure time, can influence vibration intensity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among the trunk muscles, the abdominal muscle is reported to be an important determinant for effectively performing daily life and maintaining correct posture [ 14 ]. Ultrasonography was used in studies to determine the muscular structure of the abdominal muscle in children [ 15 , 16 ], because it has the advantages of low cost, non-invasive evaluation, and deep muscle measurement [ 17 ].…”
Section: Introductionmentioning
confidence: 99%